PROFIL SISWA KORBAN BULLYING DI SMP/MTS - Maolana, Burhan; Wikanengsih, Wikanengsih; Suherman, Maya Masyita (IKIP Siliwangi, 2019)
This study aims to determine students who experience bullying at a school in Bandung. This research was conducted based on the phenomena that occur in the field. One thing that schools can do through counseling teachers is the provision of group counseling services to all students in the school and working with class teachers and subject teachers. The approach used in this research is a descriptive qualitative approach. Data collection methods are interviews and documentation of counseling teachers and students who experience bullying victims. The research subjects were 2 students who were victims of bullying and a counseling teacher. The results of the study indicate that these students experience repeated bullying so that the child's psychology is disturbed as a result of these students often skipping school, lack of motivation to learn, quiet, and lack of confidence.Keywords:Â Bullying, Students.